The Social and Economic Consequences of US Militarism - Pierre Guerlain (Revue LISA)
This article reviews the forms of US militarism as they have evolved since Eisenhower’s famous 1961 speech and presents the deleterious effects military spending has on the social and economic well-being of the United States. In particular it shows that military Keynesianism is a blind alley which does not benefit the larger economy. This article will show that militarism impacts the minds of citizens and the contents of political debates and adversely affects the image of the US abroad. It can also be argued that it fosters economic and political decline for the only superpower which is today in competition with emerging rivals.